The EU Methodology of Security and Defense Planning - M. V. Alexandrov (Vestnik MGIMO-Universiteta, 2015)
Abstract: The article examines the methodology used within the European Union when planning the security and defence policy. The author analyses the key EU documents in this field, the structure of the respective EU bodies and the corresponding decision-making process. In particular, the article looks at the security and defence planning responsibilities of the European Council, the Military Committee and the Military Staff as well as the European Defence Agency. The author conducts a comparative analysis of the EU security and defence planning methodology with that of the US and NATO. He shows that the methodology is very similar. This concerns in particular the structural composition and the logics of the planning, its geographical scope and considerable propaganda component of respective public documents. Similarly to the US and NATO, the EU defence planning relies very little on the strategic forecasting. Instead the EU makes the principle of “strategic uncertainty” the corner stone of its policies. At the same time the EU widely uses elements of “dynamic forecasting” in its planning process, especially for short term forecasting periods. Moreover, the EU moved even further than the US and NATO along this road by applying the techniques that can be described as “dynamic planning”. At the same time the methodology of the EU security and defence planning has some significant specific features. This is explained by the fact, that the EU is mostly a civilian entity and military issues play only a small, though an important role in its work. Thus priority in its planning is given to civilian methods of promoting security, and the use of military force is regarded as the last resort. That is why the main accent in the EU security and defence policy is made on such instruments as crises management, political stabilization, peacekeeping operations and engagement of other states in all sorts of security and defence partnerships. This article is prepared in the framework of the Russian Scientific Fund project 14-18-02973 “Long term forecasting of the development of international relations”.